Difficulties and Challenges in an Employment Supervision Program for Paroled Prisoners - Shoham, Efrat; Peled-Laskov, Ronit (International Journal of Criminology and Sociology, 2022)
The integration of paroled prisoners in employment is presented in the theoretical and research-based literature as one of the principal means of achieving successful re-entry by the prisoners into the community. The literature deals extensively with the correlation between integration and perseverance in employment and risk indices, the most pronounced of which is a return to crime. According to the Theory of Desistance from Crime, it is not enough for criminal activity to cease; a complex process must set in motion to bring about a change in perceptions and behaviour in all walks of life, especially regarding employment. A key program being implemented by Israel's Prisoner Rehabilitation Authority is one involving an employment guidance and supervision program for paroled prisoners. The program emphasizes employment in all its facets – placement, support during the period of employment and supervision during parole – alongside psychological treatment and rehabilitation in the community. Operating the program are employment supervisors and psychotherapists. In order to understand how the program is managed and perceived by its operators, in-depth interviews were conducted with seven psychotherapists and employment counsellors in the framework of the present qualitative-interpretive research. The article describes the perceptions of the personnel responsible for running the program during the period 2018-2020. The findings of the research highlight the difficulties and limitations the prisoners face, harmony and dissonance in the encounter between supervisors and psychotherapists, the dilemma over protection of society vs. assistance to the prisoners, employment characteristics as indicative of the rehabilitation process, and the merits of the program. The article also discusses the contribution of employment supervision to successful reintegration of paroled prisoners in normative employment and society.